2001
DOI: 10.1021/jp004012i
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Scanning Tunneling Microscopy Study of the Anodic Oxidation of Cu(111) in 0.1 M NaOH

Abstract: In situ electrochemical scanning tunneling microscopy (STM) measurements of the anodic oxidation of Cu(111) in 0.1 M NaOH are reported. Anodic oxidation is preceded, in the underpotential range, by adsorption of an ordered layer assigned to OH species. This ordered adlayer is a precursor of the oxide growing at higher potential with the copper surface reordering to mimic the structural arrangement of a (111) oriented Cu2O oxide. In the potential range of Cu(I) oxidation, a Cu2O(111) oxide film is formed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
176
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(191 citation statements)
references
References 25 publications
15
176
0
Order By: Relevance
“…1, which is similar to previous results [26][27][28][29][30]. Two well-defined anodic peaks (A1, A2) and one ill-defined one (A3) during the positive scan were assigned to the oxidation of Cu at the electrode surface to the corresponding oxides of Cu(I), Cu(II) and Cu(III), respectively.…”
Section: Preparation Of Porous Cu Filmsupporting
confidence: 90%
See 2 more Smart Citations
“…1, which is similar to previous results [26][27][28][29][30]. Two well-defined anodic peaks (A1, A2) and one ill-defined one (A3) during the positive scan were assigned to the oxidation of Cu at the electrode surface to the corresponding oxides of Cu(I), Cu(II) and Cu(III), respectively.…”
Section: Preparation Of Porous Cu Filmsupporting
confidence: 90%
“…When the potential shifted to −2.5 V, Cu(II) oxides were quickly reduced to Cu atoms, which were removable due to the reconstruction of Cu surface lattice structure by the incorporation and removal of O species and H 2 bubbles releasing. The interaction between O species (OH − in the alkaline solution) and Cu surface and the formation of Cu oxide film have been studies elsewhere [26,27]. The cycle repeated and 3D porous structure was finally formed.…”
Section: Preparation Of Porous Cu Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…The related anodic peak (A 1 ) is in alkaline electrolyte typically associated with oxidation of copper to Cu 2 O. 14,15,18,49,50 The current density increased continuously after the electrode potential reached ≈−0.1 V, indicating a high metal dissolution rate. A more detailed CV peak assignment was obtained by in situ Raman spectroscopy, and will be discussed later in this section.…”
Section: Resultsmentioning
confidence: 99%
“…2(B)). It was shown that, on the CuE substrate, protective anodic oxides in solutions of pH > 5 are formed [49]. Due to this fact, the CV of the CuE in alkaline solution (0.1 M NaOH) shows characteristic anodic and cathodic peaks that are related to the formation and reduction of these anodic oxides ( Fig.…”
Section: Roughness and Electrochemical Reactivity Of The Amalgam-allomentioning
confidence: 96%